Students' Attitudes toward Using Innovative Information Technology for Learning Based on Theory of Planned Behavior - Chiang, Feng Kuang; Wuttke, Heinz Dietrich; Knauf, Rainer; Sun, Chung Shan; Tso, Tai Cheng (International Journal of Advanced Corporate Learning (iJAC), 2009)
The main purpose of this study was to explore how IT is integrated into teaching and learning in German bachelor curriculum, and explore the university students' attitude toward the use of integration innovative information technology for learning in Germany. The data was collected by document collection and questionnaires. Multiple Regression Analysis was used to determine the three variables of behavioral intention. The results show that both attitude and subject norm are good predictors of IT for students' learning intention. Finally, results indicated TRA predicts the use innovative IT for learning intention well, though the impact of the TRA is greater than TPB.